AL QAṢȊDAH AL ‘AINIYYAH FȊ DȊWȂN AL HADDȂD LIL HABȊB ‘ABDULLAH BIN ‘ALWI AL HADDȂD WA JAMȂLUHȂ MIN AS SAJ’AH AL BADȊ’IYYAH - Syahrida, Syahrida (STIQ Amuntai, 2022)
The science of Balaghah is an integral part of the Arabic language. Through the science of balaghah, we can know and dive into how beautiful the Arabic language both in terms of pronunciation and meaning. We can also see the beauty of balaghah in the redaction of the Qur'an because in it, there are many miracles of the Qur'an in terms of the beauty of wording and meaning. This study aims to find out about the beauty of the verse of qashidah ‘Ainiyyah from the point of view of type rhymes and to determine the level (degree) of rhymes contained in Qashidah ‘Ainiyyah. This study is a study that uses a qualitative approach to the type of literature review research. Literature review is a research carried out by collecting several books related to the title, then an analysis based on the sources that have been collected. The primary Data used in this study is Qashidah ‘Ainiyyah, while the secondary data used by researchers include the book of Diwan Imamul Haddad, The Book of Syarhul ‘Ainiyyah, and The Book of Jawahirul Balaghah. The research results obtained are there are 3 types of rhymes contained in Qashidah 'Ainiyyah namely rhyme ‘mutharraf’, rhymes ‘mutawaazi’ and rhyme ‘murashsha'. In addition there are 2 levels of beauty degrees rhymes: degrees ‘ulya and degrees wustha.